The role of dialogue leadership in promoting organizational citizenship behaviors (A field study of the opinions of a group of workers at the University of Karbala) - Majeed abdulyemaah, Adil; Mzid bin Omar, Imen (Iraqi Journal for Administrative Sciences, 2024)
The study aimed to know the role of dialogic leadership at the University of Karbala in its dimensions and its impact on organizational citizenship behavior in its dimensions. The research problem was raised as one of the most important questions, which is the degree of availability of dialogic leadership and organizational citizenship behavior and what is the level of the relationship between them in terms of connection and influence. As it represented an intellectual debate between researchers, and to achieve the goal for which the study was prepared and to test the hypotheses, an adapted form was prepared and appropriate to the nature of work at the university, as the sample consisted of (123) employees, depending on the nature of their work. The statistical data was analyzed using the statistical program (Spss. V25), to test the validity and reliability, the Cronbach’s alpha coefficient was used, and to test the research hypotheses, the simple PEARSON, The researcher recommended that the university administration should increase its interest in dialogue leadership, which enhances their citizenship behavior and makes it one of the pillars of institutional work, and that employees should feel that they are the essence of the work in it, which increases their motivation and connection to their work and enhances other aspects that would enhance that behavior.